Bolometer tomography on Wendelstein 7-X for study of radiation asymmetry. (8th October 2021) - Zhang, D.; Burhenn, R.; Beidler, C.D.; Feng, Y.; Thomsen, H.; Brandt, C.; Buller, S.; Reimold, F.; Hacker, P.; Laube, R.; Geiger, J.; Regaña, J.M.García; et al.
Abstract: The algorithm for bolometer tomography at Wendelstein 7-X (W7-X) has been recently improved using a novel regularization functional, based on relative gradient smoothing of the sought radiation profile. It has been validated using radiation patterns provided by 3D modeling under real plasma conditions as phantoms and then applied to bolometer measurements performed during the first divertor operation phase of W7-X. The following results are presented: (1) edge-localized 2D radiation patterns with clearly resolved magnetic island radiation structures, (2) an up-down asymmetry in the impurity radiation that is not captured by the 3D edge plasma transport modeling, (3) reversal of the asymmetry with reversed magnetic field direction. Further analysis reveals a poloidal variation of the emissivity in the outer confined plasma region with a field-direction dependent asymmetry, also supported by the soft x-ray measurements. This asymmetry is considered to be related to asymmetric impurity distributions, driven by the pronounced ion-impurity friction force at the plasma edge where the collisionality of the W7-X plasma is sufficiently high to develop impurity asymmetry as predicted by neoclassical theory of parallel impurity transport.